KEAMANAN SOSIAL DAN KEAMANAN LINGKUNGAN DI PULAU TERLUAR DI INDONESIA: STUDI KABUPATEN KEPULAUAN RAJA AMPAT - Poltak Partogi Nainggolan (Sekretariat Jenderal DPR RI, 2012)
The Raja Ampat archipelago, a new municipality in West Papua Province, is one of Indonesia’s outer islands, which is vulnerable from any from of securitythreats, especially social and environmental security because of its natural resources potensials –in particular its coral reefs– and important position from the aspects of geopolitics and geostrategy. A study from both security point of views is currently needed in time of the rising threats to the archipelago coming from the intensifying presence of foreign investors and visitors. This study is completed with field researches, interviews, and FGD with various parties conducted in 2011.